2004
DOI: 10.1002/adem.200400047
|View full text |Cite
|
Sign up to set email alerts
|

New type of Pb‐free Machinable Soft‐Magnetic Stainless Steels with Dispersed Titanium Carbo‐Sulfide

Abstract: Although conventional free‐cutting soft‐magnetic stainless steel contains Pb to facilitate machining, the replacement and elimination of Pb is required from the standpoint of environmental protection. In this article, the authors report the development of new Pb‐free machinable soft‐magnetic stainless steels in which titanium carbo‐sulfide is used as an inclusion. The microstructural evolution, magnetic properties, corrosion resistance, machinability and mechanical properties of these new free‐cutting stainles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the toxicity of Pb is a problem from the standpoint of environmental protection. We have recently developed new types of Pb-free machinable stainless steels with dispersed titanium carbo-sulfide, 17,18) where thermodynamic database on sulfide in steel plays the vital role in alloy design. Figure 4 shows the isothermal section diagram of Fe0.21Si0.7Mn 16.5Cr0.55TiCS (mass%) alloy at 800°C.…”
Section: Alloy Design Of Fe-based Alloysmentioning
confidence: 99%
“…However, the toxicity of Pb is a problem from the standpoint of environmental protection. We have recently developed new types of Pb-free machinable stainless steels with dispersed titanium carbo-sulfide, 17,18) where thermodynamic database on sulfide in steel plays the vital role in alloy design. Figure 4 shows the isothermal section diagram of Fe0.21Si0.7Mn 16.5Cr0.55TiCS (mass%) alloy at 800°C.…”
Section: Alloy Design Of Fe-based Alloysmentioning
confidence: 99%
“…Recently, it is reported that the Ti 4 C 2 S 2 is also effective to improve the cold workability of stainless steels as well as the improvement of the corrosion resistance, because Ti 4 C 2 S 2 suppresses the precipitation of MnS and Cr 23 C 6 and scavenging C and S from the matrix [37]. In addition, it has been reported that the Ti 4 C 2 S 2 dispersion has significan effect to improve the machinability of stainless steels [38,39] and invar alloys [5], which are expected as a Pb-free machinable alloys. Several thermodynamic calculations for stainless steels and Fe-Ni based invar alloys are shown hereinafter.…”
Section: Stainless Steels and Invar Alloysmentioning
confidence: 99%
“…510) Recently, a new free-cutting soft-magnetic stainless steel with Ti 4 C 2 S 2 inclusions rather than MnS has been developed. 11) In the case of conventional free-cutting stainless steels, the corrosion resistance of the Ti 4 C 2 S 2 inclusions is higher than that of MnS inclusions. 12,13) It has been reported that the absence of anodic dissolution of Ti 4 C 2 S 2 inclusions in a conventional 18Cr-8Ni austenitic stainless steel can be attributed to the formation of a Ti-enriched oxide layer, and that no pitting initiates at the inclusions as a result.…”
Section: Introductionmentioning
confidence: 99%